Research on the Force-Sensitive Characteristic of InAs QD Embedded in HEMT - Rui-Rong Wang (MDPI AG, 2021)
A force-sensitive structure of an InAs Quantum Dot (QD) embedded in a high electron mobility transistor (HEMT) is presented in this paper. The size of an InAs QD is about 30 nm prepared by the S-K growth mode, and the force-sensitive structure is fabricated by molecular beam epitaxy (MBE). The force-sensitivity characteristic of the QD HEMT is studied by the electrical and mechanical properties. The electrical characteristics show that the InAs QD-HEMT has linear, cut-off, and saturation operating states, and produces different output currents under different gate voltages, which shows that the structure is reasonable. Furthermore, the results of the output characteristics under different pressure show that the output voltage of the QD-HEMT decreases with the increase in pressure, which indicates that the InAs QD-HEMT has a vital mechanical–electrical coupling characteristic. The output voltage of the InAs QD-HEMT in the range of 0–100 kPa shows that the sensitivity was 1.09 mV/kPa.